Night and day [compact disc, unabridged] - Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Jesse Stone novels., 2009)
Paradise, Massachusetts police chief Jesse Stone is back in Robert B. Parker's 8th installment of the Jesse Stone series.